PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, LOAN LOSS PROVISION DAN NET INTEREST MARGIN TERHADAP NON PERFORMING LOAN (Studi kasus pada bank umum konvensional di Indonesia yang terdaftar di BEI pada tahun 2008-2014) - Ginting, Join Syah Putra; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2016)
This research aims to analyze the infulence of Capital Adequacy Ratio, Loan to Deposit Ratio, Loan Loss Provision and Net Interest Margin to credit risk that measured by NPL. This research is made because there is non performing loan in many years ago. Altough NPL ratio is still under maximum limit, banks have to control the movement of the NPL ratio every years. This research uses multiple linear regression analysis to test the hypotesis. Research population used is all independent variabels data (CAR, LDR, LLP and NIM). Type of data used in the form of time series data that restricted to the data of each variable yearly starting from the period 2008 period to 2014 period.The result showed that the LDR and LLPhas significant positive effect on Non Performing Loan ratio. While CAR has no effect on the Non Performing Loan and NIM has significantÂ  negatif effect on the Non Performing Loan Ratio. In addition, it was found that the value of adjusted R square is 31,2% of the movement of NPL can be predicted from the four variables, while at 68,8% is explained by other variables outside the model. In addition the research found that the LDR, CAR and NIM, has a high variation during seven years of observation. Significant positive of LDR effect be the culprit because the instability of the LDR affecting the stability of NPL.